IDENTIFICATION OF PHILOSOPHICAL ARCHITECTURE TRANSFORMATION FORM OF PASSENGER TERMINAL BUILDING OF KERTAJATI AIRPORT: COMPARISON OF VISUAL FEATURES OF MERAK BIRD (PEAFOWL) AND MERAK DANCE - Agung Setiawan; Sri Handayani; Fitriani Fitriani (Program Studi Arsitektur S-2 Universitas Pendidikan Indonesia, 2021)
AbstractKertajati Airport in Majalengka, West Java is known to have an attractive architectural design with a characteristic expression of